Assessment of monacolin in the fermented products using Monascus purpureus FTC5391 - Ajdari, Zahra; Ebrahimpour, Afshin; Abdul Manan, Musaalbakri; Hamid, Muhajir; Mohamad, Rosfarizan; Ariff, Arbakariya (Hindawi Publishing Corporation, 2011)
Monacolins, as natural statins, form a class of fungal secondary metabolites and act as the specific inhibitors of HMG-CoA reductase. The interest in using the fermented products as the natural source of monacolins, instead of statin drugs, is increasing enormously with its increasing demand. In this study, the fermented products were produced by Monascus purpureus FTC5391 using submerged and solid state fermentations. Two commercial Monascus-fermented products were also evaluated for comparison. Improved methods of monacolins extraction and identification were developed for the assessment of monacolins in the fermented products. Methanol and ethanol were found to be the most favorable solvents for monacolins extraction due to their ability to extract higher amount of monacolin K and higher numbers of monacolin derivatives. Problem related to false-positive results during monacolins identification was solved by adding monacolin lactonization step in the assessment method. Using this improved method, monacolin derivatives were not detected in all Monascus-fermented products tested in this study, suggesting that their hypocholesterolemic effects may be due to other compounds other than monacolins.